Minister of Education and Culture Regulation number 51 of 2018 concerning the zoning system for student morality at SMA Negeri 2 Medan - Hartika, Dewi; Stepani, Gabriella; Jamaluddin, Jamaluddin; Andriani, Nisa; Yunita, Sri; Adawiah, Sriatul (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This study evaluates the impact of the zoning system on student morality at SMA Negeri 2 Medan, which is regulated by Permendikbud No 51/2018. Although it aims to equalize access to education, the implementation of the zoning system shows significant changes in students' behavior and morality. The qualitative research method was conducted at SMA Negeri 2 Medan with a focus on direct observation during Civics learning. The results revealed decreased learning motivation, lack of discipline, and reduced responsiveness to teachers' teaching as negative impacts of the zoning system. While it provides equal access to education, it also challenges the management of student morality. Conflicts arise between the implementation of zoning and efforts to shape student character, with academic selection students tending to have better character. Teachers are faced with the additional task of guiding students in ethics and manners. This research provides an in-depth understanding of the social and behavioral impacts of students in the context of education policy. While the zoning system has positive goals, additional strategies are needed to maintain and improve student morality in schools that implement this system.